Potential Pandemic of H7N9 Avian Influenza A Virus in Human - Pu, Zhiqing; Xiang, Dan; Li, Xiaobing; Luo, Tingting; Shen, Xuejuan; Murphy, Robert W.; Liao, Ming; Shen, Yongyi (Frontiers in Cellular and Infection Microbiology, 2018)
Since 2013, the H7N9 avian influenza A virus (AIV) has caused human infections and to the extent of now surpassing H5N1. This raises an alarm about the potential of H7N9 to become a pandemic problem. Our compilation of the amino acid changes required for AIVs to cross the species-barrier discovers 58 that have very high proportions in both the human- and avian-isolated H7N9 viruses. These changes correspond with sporadic human infections that continue to occur in regions of avian infections. Among the six internal viral genes, amino acid changes do not differ significantly between H9N2 and H7N9, except for V100A in PA, and K526R, D627K and D701N in PB2. H9N2 AIVs provide internal genes to H7N9. Most of the amino acid changes in H7N9 appear to come directly from H9N2. Seventeen amino acid substitutions appear to have fixed quickly by the 5th wave. Among these, six amino acid sites in HA1 are receptor binding sites, and PB2-A588V was shown to promote the adaptation of AIVs to mammals. The accelerated fixation of mutations may promote the adaptation of H7N9 to human, but need further functional evidence. Although H7N9 AIVs still cannot efficiently transmit between humans, they have the genetic makeup associated with human infections. These viruses must be controlled in poultry to remove the threat of it becoming a human pandemic event.